Legal Frameworks Strengthening Democratic Participation and Public Policy for Inclusive Social Development - Althea Serafim Kriswandaru; Berliant Pratiwi (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
Legal consistency is the main requirement to ensure the effectiveness of democratic participation and consistent policy implementation at the local level of decentralized governance. This current study aims to explore the role of legal consistency in the implementation of policy in newly formed regions of decentralized governance and its implications for democratic participation and inclusive social development. The present study adopted a qualitative methodology using a normative-empirical approach and analyzed twenty-four legal and public policy documents at national and local levels using content analysis and semi-structured interviews of policymakers and experts using a purposive sampling technique. From the findings of this current study, it is revealed that legal consistency is considerably influencing policy implementation at the local level of newly formed regions, and regions with a higher capacity of legislative acts show consistent policy implementation and clear distribution of powers and functions of local authorities. Legal inconsistency causes issues of overlap and delays in the implementation of public policy. This current paper contributes to theory by advancing normative legal analysis in the field of decentralization. Practically, the findings guide regulatory harmonization efforts and legislative capacity development, concluding that legal consistency is for decentralized governance.